Multiples lines of evidence unveil cryptic diversity in the Lophostoma brasiliense (Chiroptera: Phyllostomidae) complex. Issue 1 (31st December 2022) - Esquivel, Diego A.; Pereira, Maria Joáo Ramos; Stuhler, John D.; Rossoni, Daniela M.; Velazco, Paúl M.; Bianchi, Filipe Michels
Abstract : Phenotypically similar species – often called cryptic species – represent a challenge for taxonomy and conservation biology because they are usually undetectable to scientists. To unravel these cryptic taxa, studies now employ data from different sources under an integrative approach. We present an assessment of the cryptic diversity of the Lophostoma brasiliense species complex (Chiroptera: Phyllostomidae) based on multiple lines of evidence (molecular, morphological, morphometric, and geographic data) and using molecular (ABGD, ASAP, GMYC, and bPTP) and phenotypic (distance-based approaches and Normal Mixture Model Analyses) species delimitation methods. Our analyses recognized two distinct lineages with clear allopatric distributions. One lineage corresponds to Lophostoma brasiliense with a cis-Andean distribution and the other to the formerly species Lophostoma nicaraguae with a trans-Andean distribution. The two lineages probably diverged from a vicariant speciation driven by the uplift of the Andes less than six million years ago. Our work also shows that the wide range of environmental conditions during the recent history of South America may have promoted restrictions to gene flow among the populations of Lophostoma brasiliense . Finally, we raised L. nicaraguae to species level clarifying the species limit and morphological characteristics of lineages, and we provide an emended diagnosis and comparisons between the two taxa. We highlight the need for multiple lines of evidence to solve the remaining taxonomic problems among the remaining species complexes in Lophostoma .